Pengaruh Gender, Kompleksitas Tugas, Tekanan Ketaatan, Dan Pengalaman Auditor Terhadap Pertimbangan Audit( Studi Empiris Pada Kantor Akuntan Publik di Surakarta dan D.I Yogyakarta ) - Defiani, Defiani; , Drs. Wahyono, MA, Ak (2015)
The importance of the audit judgment is to provide an opinion about the fairness of the presentation of the financial report, in accordance with financial accounting standards or generally acceptable accounting principles and the application of such standards or principles consistently . This study is aimed to determine the effect of gender , the complexity of the task , the pressure of obedience , and the auditor's experience towards audit judgment in public accounting firm in Surakarta and Yogyakarta . This survey uses primary data obtained by the questionnaire . Population in this study is taken from were all auditors who are working in the public accounting firm in Surakarta and Yogyakarta. The number of samples in this research are 35 respondents drawn by convinience sampling technique. The data analyzed using multiple regression test . The results showes that : (1) gender does not affect the audit judgment . It can be seen from the results of the t test , the gender variable tcount (1.057) is smaller than the ttable (2,042) or it can be seen from the significant value 0.299 >  = 0.05 . So , H01 and H1 are not supported statistically . (2) task complexity affects the audit judgment . It is show from the results of t-test , in which the variable complexity of the task tcount (2.190) is greater than t table (2,042) or it can be of significant value 0.036 < = 0.05. Hence , H02 and H2 are supported statistically. (3) adherence pressure has no effect on audit judgment. It can be seen from the results of the t test , known obedience pressure variable tcount ( 1.903 ) is smaller than the ttable (2,042) or it can be seen from the significant value 0.067 > = 0.05 . Therefore , H03 and H3 are not supported statistically. (4) the experience of auditor is affects on audit judgment . It is shown by the results of the t test , the variables auditors experience tcount (-2.570) is greater than ttable (-2.042) or it can be seen from the significant value of 0.015 < = 0.05 . As a resuit , H04 is rejected and H4 is supported statistically